A study of the structure of the human form in the works of both Cézanne and Picasso - علي, احسان (Basrah Arts Journal, 2025)
The structure of artistic achievements over the ages did not follow a specific path, but rather there was a very clear difference. This difference was not specific to the general structure of the artistic achievement, but rather some elements were dealt with in several ways and various methods according to intellectual and scientific developments. The human figure is one of these important elements in the history of fine art and gains its importance through documenting events and scenes since the most ancient times through the presence of the human figure as a basic element in the structure of the achievement and according to what the subject to be documented requires. This is what makes the human figure enjoy multiplicity and diversity in artistic styles according to the nature of the environment to which the artist belongs and everything related to the ideological dimensions of the society to which he belongs. This research is considered a study in identifying the structure of the human figure in the works of both Cézanne and Picasso.